Evaluating the Implementation of Formal Early Childhood Education in Pesantren in South Sulawesi - Kasmah, Kasmah; Mardiyanti Syam, A. Sri; Tajuddin, Mawaddah; Hafid, Abd; L, Idrus (Nazhruna: Jurnal Pendidikan Islam, 2023)
This article discusses the implementation of the Program Diniyah Formal (PDF) organized by four Islamic boarding schools in South Sulawesi, namely PDF Al-Junaidiyah in Bone Regency, PDF Asadiyah in Sengkang Regency, PDF Mangkoso in Barru Regency, and PDF Nahdatul Ulum in Maros Regency. This research is evaluative research using a discrepancy model. The purpose of this study is to examine whether there is a gap between the standards/criteria for implementing PDF and its actual implementation. The indicators used in this study are derived from the criteria for high school education set by the National Secondary School Accreditation Body (BAN-SM), which is divided into four aspects: graduate quality, learning process, teacher quality, and madrasah management. The instruments used include questionnaires, interview guidelines, and documentation guidelines. Based on the results, the evaluation of the quality of PDF graduates at Islamic boarding schools in South Sulawesi is classified as good. Meanwhile, the evaluation of the PDF learning process at Islamic boarding schools in South Sulawesi is classified as fair. Additionally, the evaluation of the quality of PDF teachers at Islamic boarding schools in South Sulawesi is classified as fair, while the evaluation of PDF madrasah management at these schools is also classified as fair.